The accidental taxonomist - Hedden, Heather (Information Today, 2010)
The Accidental Taxonomist is the most comprehensive guide available to the art and science of building information taxonomies. Heather Hedden-one of today's leading writers, instructors, and consultants on indexing and taxonomy topics-walks readers through the process, displaying her trademark ability to present highly technical information in straightforward, comprehensible English.